Continuous quality improvement in HIV and TB services at selected healthcare facilities in South Africa - Sisanda Gaga; Nokuzola Mqoqi; Raymond Chimatira; Singilizwe Moko; Jude O. Igumbor (AOSIS, 2021)
Background: Continuous quality improvement (CQI) is essential for HIV and tuberculosis (TB) services. Similarly, a thorough understanding of the requirements and impact of CQI is critical to its successful institutionalisation. However, this is currently lacking. Objectives: The objective of this study is to describe the CQI implementation process and examine its effect on HIV and TB service delivery at selected primary healthcare facilities in two South African districts. Method: We used a separate sample, pre- and post-test, quasi-experimental study design based on data collected from the clinical audit of patient cohorts seen in 2014 and 2015 respectively. Quality was measured based on the extent to which prescribed services were provided. Tailored CQI interventions were implemented based on service delivery gaps identified by the 2014 CQI audit. Data were summarised and analysed using a combination of univariate and multivariate analysis. Results: The services identified as low quality were related to opportunistic infections management and laboratory practices. Compliance to prescribed service items in antiretroviral treatment initiation and monitoring, pharmacy and laboratory management, exceeded 70% across study sites. Over 80% of low quality service delivery items were optimised in less than six months with targeted quality improvement support. Conclusion: The observed improvements signal the effectiveness of the CQI approach, its capacity to rapidly improve under-performance, its high replicability and the need to provide quality maintenance support to sustain or improve healthcare facilities performing well. The study strongly underscores the need to improve the management of opportunistic infections and complications, particularly TB.